Peran Literasi Digital dalam Pengembangan Jiwa Kewirausahaan Mahasiswa Pendidikan Bahasa dan Sastra Indonesia di Era Ekonomi Digital - Anggia Jelita; Siti Enik Mukhoiyaroh Bambang; Nurhasanah Nurhasanah; Yayu Hanipah; Juan Beryl (MAN 4 Kota Pekanbaru, 2026)
Digital literacy has become an essential competency for university students in the digital economy era. This study aims to examine the role of digital literacy in developing the entrepreneurial mindset of Indonesian Language and Literature Education students. The study employed a literature review approach by analyzing scholarly journals, research articles, and other relevant academic sources. The findings indicate that digital literacy contributes to enhancing students’ entrepreneurial interest, creativity, innovation, adaptability, and readiness to engage in entrepreneurial activities. It also supports the development of entrepreneurial characteristics, including self-confidence, problem-solving skills, and risk-taking ability. Furthermore, students of Indonesian Language and Literature Education have various entrepreneurial opportunities in the digital economy, such as content creation, copywriting, editing services, online tutoring, and social media management. Digital platforms also facilitate business promotion, communication, and marketing. Therefore, strengthening digital literacy is essential for fostering entrepreneurial mindsets and preparing students to become creative, adaptive, and competitive individuals in the digital economy era.